Effects of pumice additions on thermal and mechanical behaviors of epoxy resin - İbrahim Kırbaş (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
In this study, thermal conductivity, mechanical properties, and thermal degradation of pumice-added epoxy materials were investigated. 2%, 4%, 6%, 8%, and 10% of pumice was added to the epoxy resin (EP) % by weight. Various types of analyses and tests were conducted to determine the thermal conductivity, mechanical properties, and thermal degradation of these epoxy materials. The tests and analyses proved that the addition of pumice leads to a decrease in the thermal conductivity coefficient and density of the pure EP material. It also increases the degree of hardness. The addition of pumice had a positive effect on mechanical properties. Compared to pure EP, it increased the tensile strength, Young’s modulus, bending strength, and flexural modulus. As a result of TGA analysis it was determined that with the incorporation of pumice into the EP, its decomposition rate progressed more slowly. At 800_C, the carbon residue improved as a result of the addition of pumice.